Experiences and challenges of pre-exposure prophylaxis initiation and retention among high-risk populations: qualitative insights among service providers in Thailand - Rayanakorn, Ajaree; Chautrakarn, Sineenart; Intawong, Kannikar; Chariyalertsak, Chonlisa; Khemngern, Porntip; Olson, Debra; Chariyalertsak, Suwat (Frontiers in Public Health, 2024)
Objectives Pre-exposure prophylaxis (PrEP) has been an essential element of the national combination prevention package and included in the Universal Health Coverage (UHC) of Thailand since 2019. As a part of the national monitoring and evaluation framework, this qualitative study aims to describe experiences and barriers concerning PrEP initiation and retention among service providers from both hospital and Key Population Led Health Service (KPLHS) settings under the country’s UHC roll-out. Methods Between September and October 2020, ten focus group discussions with PrEP service providers from both hospitals and KPLHS across Thailand were conducted of which there were six hospitals, one health service center, three KPLHS. All interviews were recorded and transcribed verbatim to identify providers’ experiences, attitudes, and perceived barriers regarding PrEP service delivery in Thailand. Results Among the 35 PrEP service providers, most of them reported positive attitudes toward PrEP and believed that it is an effective tool for HIV prevention. Men who have sex with men were perceived to be the easiest group to reach while PrEP uptake remains a challenge in other key populations. Integration of a PrEP clinic with other HIV services at hospitals made most healthcare providers unable to adopt an active approach in recruiting new clients like at KPLHS settings. Challenges in delivering PrEP services included lack of public awareness, high workload, limited benefit package coverage, structural and human resources. Conclusion Additional services to address different health needs should be considered to increase PrEP uptake among harder-to-reach populations. Novel approaches to PrEP service integration and close collaboration between hospitals and KPLHS would be essential in optimizing PrEP uptake and retention. Support regarding raising awareness, expanding service coverage and access, improving facilities and workforce, and providers’ capacities are crucial for the success of the national PrEP programme.